Foreign company and national sovereigntyA vision of security threats and confrontation strategy (قضايا سياسية, 2025)
Corporations have become the largest players in international politics, wielding significant economic and political influence in both developed and developing countries. They have entered important strategic sectors such as security and warfare, and have become a force that has begun to challenge the state in its functions, presenting itself as an alternative to the state in a globalized world. They seek to displace the state from the throne of sovereignty. Multinational corporations work to weaken the state by adopting policies that conflict with their interests, and conversely, they strengthen the state by providing a stable and secure environment for the interests and investments of these corporations.